Overweight and obesity in preschool children in Turkey: A multilevel analysis - LÜLECİ, NİMET EMEL; HIDIROĞLU, SEYHAN (My University, 2022)
Childhood obesity/overweight is a worldwide concern and its prevalence is increasing in many countries. The first aim of this study is to analyse the trends in overweight and obesity among children under the age of five in Turkey based on the new World Health Organization (WHO) standards, using data from the \"five-round of the Turkey Demographic and Health Surveys\" (TDHSs). The second aim is to examine whether or not the maternal/household and individual-level factors are associated with overweight/obesity using TDHS 2003, 2008, and 2013 datasets. A total sample of 14,231 children under the age of five were extracted from the TDHS in 1993, 1998, 2003, 2008, and 2013 to determine the prevalence of the trend. Pooled data from 8,812 children were included in the analysis to examine factors associated with overweight/obesity. Taking into account the clustered data structure, multilevel logistic regression models were utilised. In 1993, 1998, 2003, 2008, and 2013 the prevalence of overweight children was 5.3%, 4.9%, 10.0%, 11% and 11.6%, respectively. The factors that were independently associated with overweight/obesity were as follows: living in single-parent households (adjusted odds ratio (aOR) = 2.27, 95%CI = 1.21-4.26), compared to living in dual-parent households; having an obese mother (aOR = 4.25, 95%CI = 1.73-10.44), overweight mother (aOR = 3.15, 95%CI = 1.29-7.69), and a normal-weight mother (aOR = 2.70, 95%CI = 1.11-6.59) compared to having an underweight mother; being aged between 13-24 months (aOR = 1.72, 95%CI = 1.30 to 2.27), compared to being aged 0-12 months; male gender (aOR = 1.30, 95%CI = 1.11 to 1.53); being stunted (aOR = 2.18, 95%CI = 1.74 to 2.73); high birth weight (aOR = 1.55, 95%CI = 1.08 to 2.23) compared to low birth weight. In addition, overweight was higher in children of mothers who had completed primary school (aOR = 1.21, 95%CI = 1.01 to 1.59) than children of mothers who had not completed primary school. These findings reveal that, over the years, there has been a substantial increase in obesity/overweight among children which demonstrates the importance of evaluating the overweight indicators at the maternal/household level.
Keywords: Sosyal ve Beşeri Bilimler; Sosyoloji; Demografi; Social Sciences and Humanities; Sociology; Demography; DEMOGRAFİ; Sosyal Bilimler Genel; Sosyal Bilimler (SOC); KAMU, ÇEVRE VE İŞ SAĞLIĞI; SOSYAL BİLİMLER, BİYOMEDİKSEL; DEMOGRAPHY; SOCIAL SCIENCES, GENERAL; Social Sciences (SOC); PUBLIC, ENVIRONMENTAL & OCCUPATIONAL HEALTH; SOCIAL SCIENCES, BIOMEDICAL; Safety Research; General Social Sciences; Health (social science); Life-span and Life-course Studies; Public Health, Environmental and Occupational Health; Occupational Therapy; Epidemiology; Social Sciences & Humanities; Health Sciences; Child Health and Nutrition; Obesity; Maternal and Child Health; NUTRITIONALLY STUNTED CHILDREN; NORMAL-WEIGHT OBESITY; BODY-MASS INDEX; QUALITY-OF-LIFE; FAMILY-STRUCTURE; CHILDHOOD OVERWEIGHT; GROWTH STANDARDS; BIRTH-WEIGHT; SAO-PAULO; PREVALENCE